2019
DOI: 10.1007/s12119-019-09636-0
|View full text |Cite
|
Sign up to set email alerts
|

“Hunting on the Streets”: Masculine Repertoires Among Israeli Clients of Street-Based Sex Work

Abstract: In this article, I discuss the unique masculine repertoire of Israeli clients of streetbased sex work. In doing so, I aim to reveal the deep meaning of sex consumption on the street while reflecting on the way in which universal and local masculine repertoires are negotiated and contested. Based on a discourse analysis of online sexual reports, the article focuses on clients' metaphoric language of themselves as hunters when describing sexual encounters on the street, arguing that the hunting metaphor has beco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 56 publications
(61 reference statements)
0
14
0
Order By: Relevance
“…Birch argues that most clients do not exhibit hypermasculinity, and that clients, far from being unemotional, attend to their emotional needs by seeking providers (Birch et al 2017). Lahav Raz studied how clients in online forums talk about their exploits in seeking street workers and found that they performed power and validated their masculinity more in relation to other men than to women (Lahav-Raz 2019a). While client attitudes toward gender equality are but one component of masculine repertoires, they are key to understanding how certain groups of men may define themselves in relation to women.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Birch argues that most clients do not exhibit hypermasculinity, and that clients, far from being unemotional, attend to their emotional needs by seeking providers (Birch et al 2017). Lahav Raz studied how clients in online forums talk about their exploits in seeking street workers and found that they performed power and validated their masculinity more in relation to other men than to women (Lahav-Raz 2019a). While client attitudes toward gender equality are but one component of masculine repertoires, they are key to understanding how certain groups of men may define themselves in relation to women.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A recent systematic review of the qualitative literature about MWPWS suggests that their diverse experiences are at once gendered, sexual, intimate, consumerist, and related to power relations, and social stigma (Prior & Peled, submitted for publication B ). Thus, for example, studies show that SFP enables MWPWS to fulfill their sexual desires (Huysamen, 2019 ), and boost their sense of masculinity (Hammond & van Hooff, 2019 ; Lahav-Raz, 2019a ). However, other studies have found that MWPWS may also experience a sense of compromised sexual potency and flawed masculinity when paying for sex (Prior & Peled, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Coy et al (2007) have found that attitudes of male entitlement may play a role in how men justify the commodification of sex, as buyers often explain that sex is something “to be expected and accepted” when asked why they purchase sex. Researchers investigating an Israeli online platform identified johns referring to themselves as “hunters” when discussing their sexual encounters with women (Lahav-Raz, 2020). The attitude that they are “hunting” women suggests a gendered belief in a biological need for sexual pleasure (Lahav-Raz, 2020).…”
Section: Sex As a Commoditymentioning
confidence: 99%